Resistance Monitoring of Nilaparvata lugens Stall against Pymetrozine Insecticide with Determination of Diagnostic Concentrations - Sri Murtiati; Udi Tarwotjo; Rully Rahadian (Biosaintifika: Journal of Biology & Biology Education, 2021)
Nilaparvata lugens Stall is one of the main insect pests on rice crops. Intensive control of this pests using insecticides has resulted in the development of insect resistance. This study aimed to find out the level of resistance of the N. lugens population to pymetrozine insecticides by determining the diagnostic concertations. N. lugens was collected from five endemic areas in Central Java Province from October 2019 to June 2020. The data from the bioassay test were analyzed with probit analysis to obtain the LC50 value. The results of the sensitivity test showed that the Kajen population has the highest RF value (2.47), while the Karanganyar population which has the lowest RF value (1) was the most sensitive population. The determined diagnostic concentration was LC95 = 25.52 ppm with the lowest concentration limit of 7.67 ppm and the highest of 30.05 ppm. To conclude, the determined diagnostic concentration (LC95 = 25.52 ppm) is effective for detecting the susceptibililty of N. lugens population. This finding would be beneficial for monitoring resistance of N. lugens population against pymetrozine insecticides in the field.